EPCO-44. SPATIAL TRANSCRIPTOMICS ENABLES STATISTICAL MODELING OF SEX DIFFERENCE IN GENE CO-EXPRESSION NETWORK AND IMMUNE LANDSCAPE OF GLIOBLASTOMA - Hao, Yue; Baker, Angela; Reid, George; Luo, Jingqin; Hilbush, Brian; Otero, Marcos; Streck, Christopher; Fink, Karen L; Snipes, George J; Mickey, Bruce E; Sloan, Andrew E; Barnholtz-Sloan, Jill S; et al. (Neuro-oncology (Charlottesville, Va.), 2024)
Glioblastoma (GBM) is characterized by inter- and intra-tumor molecular heterogeneity and demonstrated cell plasticity. Sex differences have been observed in various aspects: a male:female GBM incidence ratio is 1.6:1; standard of care treatments (debulking, radiation, and temozolomide) benefit females more than males. 14 human GBM samples from two study sites were subject to spatial profiling on the Vizgen Merscope platform to examine whether distinct biological and therapeutic niches in GBM were evident, to understand how the tumor microenvironments (TME) contributed to the heterogeneity of GBM, and to interrogate sex difference in the immune landscape of GBM. Multiple sets of spatial probes were designed to capture the cell identities (cancer stem cells, astrocytes, oligodendrocytes, microglia, macrophages, etc.) and the spatially-resolved expression patterns of genes with different functions. Two of the 14 GBM samples were also profiled on another FISH-based spatial platform (Veranome). The data from the two platforms exhibited a linear correlation. We explored the gene-gene co-expression network, and calculated the interaction probabilities between genes which were then compared for sex difference. We found that female samples showed significantly lower (two-fold) CD4+/CD8A+ T-cell count ratios than male samples. We also observed sample-specific spatial niches of different GBM cell subtypes and immune cell populations. Our large-scale spatial transcriptomics study revealed intrinsic sex-based differences in immune response to tumor and illuminated microenvironmental influences on GBM.